ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK KENDARAAN BERMOTOR (PKB) PADA UNIT PELAYANAN PENDAPATAN DAERAH (UPPD) PONTIANAK WILAYAH II - Dwi Widyastuti, Reni; Anggraini , Mira (Program Studi Akuntansi Universitas Panca Bhakti, 2021)
This study aims to determine the effect of local taxpayer awareness, tax socialization, tax sanctions and income levels on taxpayer compliance in paying motor vehicle taxes at UPPD Pontianak Region II. The data collection in this research is by using interview, observation, and questionnaire (questionnaire) methods. There are several research methods used in this study, including data quality tests consisting of validity and reliability tests, classical assumption tests consisting of normality tests, multicollinearity tests, and heteroscedasticity tests, and hypothesis testing consisting of multiple linear regression analysis. , t test (partial test), f test (simultaneous test), and coefficient of determination (Adjusted-R2). The results of this study indicate that the level of income affects taxpayer compliance in paying motor vehicle taxes at UPPD Pontianak Region II. Meanwhile, awareness of local taxpayers, socialization of taxation, and tax sanctions have no effect on taxpayer compliance in paying Motor Vehicle Tax at UPPD Pontianak Region II.